Globalization, environmental damage and the Corona pandemic: Lessons from the crisis for economic, environmental and social policy - Bianca Blum; Karl Justus Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2020)
The rapidly expanding corona pandemic in 2020 has largely brought the world to an economic stagnation. The impact on the environment, especially on air quality, from almost suspended air traffic, idle industry and economic lockdown is enormous, but also the economic and social consequences of the crisis. This state of stagnation hardly appears to be economically and socially sustainable. However, we should ask ourselves right now what we can learn from the situation in order to question globalization, better intercept future comparable crisis situations and take the step towards more sustainable development on an ecological, economic and social basis. The paper identifies the areas of externality management to improve environmental quality, digitalization and network expansion as well as basic income as central concepts that need to be addressed in and after the crisis. Concrete concepts are suggested and discussed at the end of the paper.
Keywords: H12; H23; H53; 330; corona crisis management; basic income; environmental politics; pandemics; globalization; public policy